PENGARUH GAYA KEPEMIMPINAN SITUASIONAL TERHADAP MOTIVASI KERJA (STUDI PADA CV. SIRO PAGER ABADI KOTA MALANG JAWA TIMUR) - Nur Huda, Amirullah Afif (Jurnal Ilmiah Mahasiswa FEB, 2016)
This research aims to understand and analyze the influence of leadership circumstantial against motivation of work. The research is explanatory research describing a causal relation between many variabels through the testing of hypothesesThis research using samples from 54 respondents taken from all the employees in cv siro pager abadi, malang city, east java. The sample techniques used in research is sampling saturated (census). Sampling saturated is a technique sample determination if all members of the population used as samples. Data collection method in this research using a questionnaire that measured by likert scale. A test that is used to test instrument this study of the validity , reliability test , and the assumption classic. Test the hypothesis carried out using t test or partial evaluation and the dominant. Analysis techniques data using linear regression multiple analysis.The research by steps described above the results that based on the results of the analysis linear regression multiple by using test t can be concluded : 1. Leadership circumstantial behavior the influential positive and significantly to motivation work. 2. Leadership circumstantial behavior relations have had a positive impact and significant impact on motivation work. While dominant test it can be concluded: 1. Leadership circumstantial behavior duty influential dominant to motivation work. This shows that Leadership is situational influence on Work Motivation that is in CV Siro Pager Abadi, Malang City, East Java.Keywords: Leadership is Situasional, Work Motivation